PERAN KOMUNIKASI KELUARGA DALAM MENGONTROL PENGGUNAAN GADGET PADA ANAK USIA DINI DI KECAMATAN PERCUT SEI TUAN - Afni Apriani; Nursapia Harahap (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Family communication is inseparable from the relationship between parents and children. In a family, not only parents but also children use gadgets. In fact, almost the average parent associates the use of gadgets with early childhood. Of course this is a challenge in establishing good communication so that parents can control the use of these devices so that their use remains within reasonable limits. This study aims to determine the role of communication used by parents in controlling the use of gadgets in early childhood in Percut Sei Tuan District. In this study used a qualitative method with a phenomenological approach. Then the researcher obtained the data by using observation, interview and documentation techniques. The source of information in this research is Percut Sei Tuan's parents. Data analysis was carried out descriptively and variation techniques and reliability tests were used for validity. The results of this study indicate that in a family, parents control the decision-making process about what children do.